PELATIHAN PEMBUATAN TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) SEBAGAI UPAYA PENGEMBANGAN PRODUK PANGAN LOKAL DI DESA PERIGI KECAMATAN SUELA LOMBOK TIMUR - Affan Gaffar; Yuliatin Hasfiani; Ziana Warsani; Soufa Malita; Lalu Amrullah; Rahayu Safitri Rahman; Nia Ulfa Madani (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community engagement program aims to strengthen the capacity of Perigi Village residents in East Lombok, Indonesia, to process cassava into MOCAF (Modified Cassava Flour) through hands-on training and the application of basic technological transfer. The program commenced with theoretical dissemination addressing the potential of cassava as a value-added local commodity and the function of MOCAF as a gluten-free wheat flour substitute. Training stages included raw material selection, fermentation, drying, milling, and product formulation using MOCAF. The results indicated a significant improvement in participants’ technical knowledge and operational skills related to standardized MOCAF production processes. Furthermore, the demonstration of MOCAF-based brownies increased participants’ interest in developing local food businesses. Overall, this activity contributed to enhancing community competence in food diversification, adding economic value to local commodities, and strengthening the village economy.